Dual Credit Markets and Household Access to Finance : Evidence from a Representative Chinese Household Survey - Cull, Robert (World Bank, Washington, DC, 2015)
Using a new and representative data set of Chinese household finance, this paper documents household access to and costs of finance, along with their correlates. As in most developing countries, informal finance is a crucial element of household finance, and wealth tends to be associated with better access to formal and informal finance. Better financial knowledge shifts loan portfolios toward formal sources relative to informal ones. Connections to the Communist Party are associated with significantly better access to finance in rural areas but not in urban areas. A larger social network is positively associated with access to informal finance. Controlling for household characteristics, rural residents pay interest rates on loans similar to urban residents. Younger residents pay higher rates, while households on firmer economic footing face lower rates. Taking financial classes and college education is associated with higher interest rates for urban residents, suggesting perhaps that financial knowledge coincides with greater demand for credit in areas with more economic opportunity. Overall, the findings suggest that Chinese residents face dual credit markets, with the poor, young, those with poor financial knowledge, and those with larger family sizes relying much more on informal finance, while others are better able to access formal finance.